The Influence of Repair Capacity on the Academic Energy of College Students - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
The present study analyzes the relationship between repair and vigor in first-year university students in Montería, using a simple linear regression model. It is based on the premise that students’ ability to adjust and correct their learning strategies positively influences their level of academic vigor, understood as the energy, motivation, and resistance with which they face their educational activities. From the analysis of a sample of 233 university students, it was found that repair has a positive and significant effect on vigor, with a coefficient of 0.1721 (p < 0.01). The validation of the model by statistical tests confirms compliance with the linear regression assumptions, ensuring the reliability of the results. It is concluded that students who implement repair and adjustment strategies in their learning process tend to experience higher levels of vigor, which highlights the importance of strengthening self-regulation mechanisms and continuous improvement strategies in higher education.